Modeling analysis of the correlation between duality innovation and multinational enterprise performance - Li, Xinran; Chen, SzeTing (Frontiers in Psychology, 2022)
In this study, we investigate how the influence of dual innovation has an effect on the productivity of multinational enterprises (MNEs). Because of the rise of the knowledge-based economy, the capacity of multinational corporations (MNCs) to innovate technologically has become an increasingly important component in determining the extent to which they are able to compete in the global market. Models of Duality Innovation and Multinational Enterprise Performance with a Measurement of Corporate Risks from 2000 to 2015 were developed using corporate finance literature and data. The models show an array of positive relationships between the duality innovations, multinational enterprise performance. Furthermore, there has been an increasing level of corporates risks over the years when measured by both the duality innovation and multinational enterprise performance metrics. This article discusses the findings of this research project, as well as explaining how they can be useful in understanding multinational enterprise performance while also explaining how to determine a potential risk profile for individual or multiple companies. This knowledge is valuable because it helps us understand why some corporations succeed which others fail.